Early juvenile development of Armases rubripes (Rathbun 1897) (Crustacea, Brachyura, Sesarmidae) and comments on the morphology of the megalopa and first crab - Fransozo, Maria Lucia Negreiros [UNESP]; Fernandes, Camile Sorbo [UNESP]; Silva, Stella Maris Januário da [UNESP]; Fransozo, Adilson [UNESP] (Int Science Services/balaban Publishers, 2011)
This article provides a description of the early juvenile stages of Armases rubripes and indicates some differences and additional details found in the megalopa and first juvenile crab stage compared with previous descriptions. The main characters that permit identification of the subsequent juvenile stages were assessed, as well as the moult interval and increment during successive moults and the beginning of development of the secondary sexual features. Megalopae of A. rubripes were collected from the Ubatuba region, São Paulo, Brazil using plankton and neuston nets. Morphological changes in body parts have been recorded for each stage and sex, as well as the duration of the intermoult period was noted. Possible effects of laboratory holding time on growth were checked by means of analysis of covariance. The importance of standardization of the terminology of setae is emphasized.
Keywords: Larval stage; Morphological description; Neuston; Sexual differentiation